2020
DOI: 10.30621/jbachs.2020.930
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Barriers to Incident Reporting for Doctors and Nurses in a University Hospital’s Surgery Departments

Abstract: Purpose: To assess awareness and use of the incident reporting system among doctors and nurses working in hospital surgery departments and to identify the reasons inhibiting incident reporting.Methods: It was used a cross-sectional study design. The study population comprised doctors and nurses working in the surgery departments of a university's adult and children's hospital. A form including an incident reporting questionnaire was administered to the population.Results: Compared to doctors, nurses were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although a well-functioning reporting system is central to patient safety (Archer et al , 2017; Radhakrishna, 2015), health-care employees tend to avoid reporting for a multitude of reasons, such as fear of punishment, damage to reputation, humiliation, malpractice lawsuits, disciplinary action by a licencing board, limited follow up after reporting or loss of job. Furthermore, it is well documented that many health-care employees lack an understanding of what should be reported and how the reported incidents will be analysed or lead to changes that will improve patient safety (Archer et al , 2017; Flott et al , 2018; Kaya et al , 2020; Krouss et al , 2019; Naome et al , 2020); indeed, health-care employees in Kuwait and the wider Arab region are not exceptions in this regard. A recent study from Kuwait (Ali et al , 2018) and a systematic review from the Arab countries (Elmontsri et al , 2017) concluded that non-punitive responses to error, reporting of events and open communication are poorly practised within organisations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a well-functioning reporting system is central to patient safety (Archer et al , 2017; Radhakrishna, 2015), health-care employees tend to avoid reporting for a multitude of reasons, such as fear of punishment, damage to reputation, humiliation, malpractice lawsuits, disciplinary action by a licencing board, limited follow up after reporting or loss of job. Furthermore, it is well documented that many health-care employees lack an understanding of what should be reported and how the reported incidents will be analysed or lead to changes that will improve patient safety (Archer et al , 2017; Flott et al , 2018; Kaya et al , 2020; Krouss et al , 2019; Naome et al , 2020); indeed, health-care employees in Kuwait and the wider Arab region are not exceptions in this regard. A recent study from Kuwait (Ali et al , 2018) and a systematic review from the Arab countries (Elmontsri et al , 2017) concluded that non-punitive responses to error, reporting of events and open communication are poorly practised within organisations.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many ways to enhance reporting systems, the selection of improvement strategies should address what is lacking. Health-care employees should be provided with high-level information on the types of incidents, the results of the analysis and what actions have been taken in response to the incidents reported (Archer et al , 2017; Kaya et al , 2020). One could claim that this strategy might not be of high impact in Kuwait, considering that “feedback and communication about error” was identified as an area of strength (Ali et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These responsibilities are mere add-ons to their already brimming schedules, and the meager budget, if any, further hinders program implementation and their engagement in essential training.Inadequate time dedicated to engaging in patient safety-focused activities of frontline healthcare personnel 12 could also explain why some patient and direct care indicators receive lower reporting than others like falls, medication errors, adverse drug events, and missed care. Reporting and contributing to learning systems can become a burden for nurses and physicians with inhumane workloads, [13][14][15] further exacerbating the issue.Inconsistencies in available data can be attributed to the lack of a mature patient safety culture, resulting in reluctance to report indicators. These indicators are often regarded as a reflection of poor performance or incompetence.…”
mentioning
confidence: 99%
“…Inadequate time dedicated to engaging in patient safety-focused activities of frontline healthcare personnel 12 could also explain why some patient and direct care indicators receive lower reporting than others like falls, medication errors, adverse drug events, and missed care. Reporting and contributing to learning systems can become a burden for nurses and physicians with inhumane workloads, [13][14][15] further exacerbating the issue.…”
mentioning
confidence: 99%